2019
DOI: 10.4274/tpd.galenos.2019.6373
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of the Seropositivity Rate of Toxoplasmosis and Clinical Results in Pregnant Women That were Admitted to a Tertiary Health Institution Between 2012 and 2017 in Turkey

Abstract: The aim of this study was to determine the frequency of toxoplasmosis in pregnant women who were admitted to our hospital in their first trimester and to contribute to screening and management strategies by evaluating clinical outcomes. Methods: In this retrospective study, women in their first trimester of pregnancy who were aged between 15-49 years, admitted to the Mersin University Medical Faculty Gynecology and Obstetrics outpatient clinic between 2012-2017, and screened for Toxoplasma gondii immunoglobuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A recent study performed in Mersin reported high ATI rates of up to 7.6% in pregnant women. This result can be explained by the region's high refugee population, climate characteristics and eating habits (17). without antenatal screening, these cases will remain undiagnosed and untreated (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study performed in Mersin reported high ATI rates of up to 7.6% in pregnant women. This result can be explained by the region's high refugee population, climate characteristics and eating habits (17). without antenatal screening, these cases will remain undiagnosed and untreated (23,24).…”
Section: Discussionmentioning
confidence: 99%